The Charter of the Hudson's Bay Company, was lately laid before five of the most eminent lawyers in England with some queries, as to the legal effect of various clauses . [electronic resource]. ([Montreal? : s.n.)
Title on added t.p.: La charte de la Compagnie de la Baie d'Hudson a dernièrement été soumise a l'examen [sic] de cinq des avocats les plus célèbres de l'Angleterre, avec quelques questions relatives à l'effet légal que pourroient avoir plusieurs des articles qu'elle contient . Text in English and French. Signed: Samuel Romilly, William Cruise, G. S. Holroyd, J. Scarlett, John Bell. Electronic reproduction. Mode of access: Internet. 44